Towards an efficient cost control in public secondary schools in Nigeria: an empirical application of the systems theory (2011)
In many developing countries like Nigeria, secondary education is heavily financed from State budgets. Although it is government's desire to provide increased access to secondary education in the face of limited resources, the cost of these increases has mode the continues expansion of secondary education unsustainable. Such has necessitated the need to improve control over cost of public education in order to provide increased access to all eligible school-age children. This paper examined the application of System's, theory to the control of unit cost in public secondary schools in Nigeria. The study found that efficient cost control and increased access can be achieved through adequate knowledge with the application of Systems theory. It therefore recommended the adoption of System's theory as a strategies framework for reducing unit cost and increasing access to secondary education in the face of limited financial conditions